Molecular cloning, tissue distribution and nutritional regulation of four acyl-coenzyme A oxidase (acox) isoforms in Scylla paramamosain - Lin Zhideng; Lan Jinjie; Lin Huangbin; Huang Chaoyang; Zhang Mingyao; Huang Qincheng (Frontiers in Marine Science, 2024)
As rate-limiting enzymes of peroxisomal β-oxidation, acyl-coenzyme A oxidase (ACOXs) play vital roles in maintaining energy homeostasis and regulating reactive oxygen species (ROS) metabolism. However, there are no studies on the functions of ACOXs in crustaceans. In the present study, four full-length cDNA sequences of acoxs , namely the acox-1a (2403 bp), acox-1b (2733 bp), acox-3a (2878 bp) and acox-3b (3445 bp), were successfully isolated from mud crab Scylla paramamosain , which encoded 666, 673, 701 and 658 amino acids, respectively. Sequence analysis showed that the ACOX-1a, ACOX-1b and ACOX-3a possessed conserved structural domains like FAD-binding motif, fatty acyl CoA oxidase domain and peroxisomal targeting signal, while the ACOX-3b lacked peroxisomal targeting signal. Results of phylogenetic tree indicated that the four ACOXs of mud crab grouped gathered with their corresponding orthologues from crustaceans. The acox-1a , acox-3a and acox-3b were highly expressed in hepatopancreas, and the acox-1b was mainly distributed in muscle and hepatopancreas. Compared with feeding groups, the expression levels of acox-1a , acox-3a and acox-3b in hepatopancreas and acox-3a in muscle were markedly up-regulated in fasting groups, suggesting that the acoxs had significant effects in modulating energy balance during fasting. In addition, fasting significantly increased the transcriptional levels of nuclear factor erythroid 2-related factor ( nrf2 ) and its downstream antioxidant genes (catalase ( cat ), glutathione peroxidase ( gpx ) and glutathione S-transferase ( gst )) to improve antioxidant capacity for removing excessive ROS produced by ACOX-mediated peroxisomal β-oxidation. These results would be conducive to providing new insights into evolutionary characteristics and functions of acoxs in crustaceans.

Molecular cloning and characterization of three carnitine palmitoyltransferase (cpt) isoforms from mud crab (Scylla paramamosain) and their roles in respond to fasting and ambient salinity stress - Zhideng Lin; Chaoyang Huang; Zhengrui Zhuo; Jun Xie; Hongliang Lan; Bixing Hu; Chengkang Zhang; Kunhuang Han; Weiqing Huang (Frontiers in Marine Science, 2024)
As rate-limiting enzymes of β-oxidation of fatty acids in mitochondria, the carnitine palmitoyltransferase (CPT) played an important role in regulating energy homeostasis of aquatic animals. However, there was very little research on β-oxidation of fatty acids in crustaceans. In the present study, the full-length cDNA sequences of cpt-1a , cpt-1b and cpt-2 were isolated from the hepatopancreas of Scylla paramamosain , and contained 4206, 5303 and 3486 bp respectively. Sequence analysis showed that the CPT-1A, CPT-1B and CPT-2 encoded proteins with 777, 775 and 672 amino acids respectively, and only the CPT-1A possessed a transmembrane region. In addition, both the CPT-1B and CPT-2 contained conservative functional domains like N-terminal domain and acyltransferases choActase 2, while the CPT-1A lacked. The results of phylogenetic tree indicated that the CPT-1A, CPT-1B and CPT-2 of S. paramamosain gathered together with their corresponding orthologues from crustaceans. The tissue distribution exhibited that the cpt-1a was highly expressed in hepatopancreas, followed by muscle, eyestalk and cranial ganglia, and the muscle, eyestalk and heart were main expressed tissues of cpt-1b . Furthermore, the high expression levels of cpt-2 were mainly detected in hepatopancreas, muscle and heart. The transcriptional levels of cpt-1a , cpt-1b and cpt-2 were significantly up-regulated under chronic low salinity stress. Besides, at the acute low salinity stress condition, the expression levels of cpt-1a , cpt-1b and cpt-2 in hepatopancreas were dramatically increased in 14‰ and 4‰ salinity groups at the 6h and 48h, while the transcriptional levels of cpt-1a , cpt-1b and cpt-2 in muscle were signally up-regulated in 14‰ and 4‰ salinity groups at the 12h and 24h, showing an alternate response pattern. Similarly, the present study found that fasting could markedly increase the expression levels of cpt-1a , cpt-1b and cpt-2 in hepatopancreas and muscle, especially cpt-1a in hepatopancreas as well as cpt-1a and cpt-1b in muscle. The results above indicated that the cpt-1a , cpt-1b and cpt-2 played a crucial part in providing energy for coping with fasting and salinity stress. These results would contribute to enhancing the knowledge of cpt phylogenetic evolution and their roles in energy metabolism of crustaceans.

Regulatory role of myo-inositol in the ovarian development of female Chinese mitten crab (Eriocheir sinensis) - Xianyong Bu; Qincheng Huang; Ying Song; Changle Qi; Zhideng Lin; Xiaodan Wang; Meiling Zhang; Chuanjie Qin; Jian G. Qin; Liqiao Chen (Aquaculture, 2023)

Regulatory role of vitamin A in lipid metabolism and health of Eriocheir sinensis fed different vegetable oil sources - Qincheng Huang; Xiaodan Wang; Zhideng Lin; Jiadai Liu; Han Wang; Cong Zhang; Zhenyu Du; Jianguang Qin; Liqiao Chen (Aquaculture, 2023)